Pengaruh Npf dan Fdr Terhadap Pendapatan Operasional Bank Syariah di Indonesia - Lailatul Aria Putri; Nik Matur Rochmah (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The purpose of this study is to determine the effect of NPF, FDR on Operating Income at Bank Syariah Indonesia. With quantitative research methods using time series data. The data used is secondary data obtained from the financial reports of Islamic Commercial Banks for the 2017-2022 period. The data analysis technique is using multiple regression analysis with the Ordinary Least Square (OLS) method. From this study shows that the NPF results have no significant effect on operating income. Meanwhile, FDR has a significant influence on operating income.